The Effect Of The Use Of Information And Communication Technology On The Administrative Reform Process "A Field Study In The Directorate Of Education In Lattakia Governorate" (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aimed to study the effect of the use of information and communication technology on the administrative reform process in the Directorate of Education of Lattakia, by studying the effect of the dimensions of information and communication technology represented by devices, equipment, software, communications, networks and human resources on the administrative reform process. Where he designed a questionnaire and distributed it to a simple random sample in the Directorate of Education and its affiliated educational complexes, and the number of valid questionnaires for analysis was 134. The researcher used the statistical program Spss in conducting statistical characterization and testing hypotheses, and the researcher found a positive moral effect for the use of both devices, equipment and human resources. On the process of administrative reform, the order of the dimensions of information and communication technology in terms of strength of influence was as follows: hardware and equipment, human resources, networks and communications, software. The researcher recommended strengthening the strengths and avoiding the weaknesses, and the need to immediately start activating the information and communication technology system in order to contribute to the administrative reform process in the Directorate.